A Study of the Relationship between Professional Communication and Professional Commitment in Operating Room Nurses - Hamed Parnikh; Camellia Torabizadeh; Majid Najafi Kalyani; Mitra Soltanian (Hindawi Limited, 2022)
Background. Operating rooms are among the most complex clinical environments in hospitals where teamwork and professional communication play a very important part. Professional commitment is an influential factor in the personnel's professional communication and can affect the outcomes of healthcare services. Objective. The present study aims to investigate the relationship between professional communication and professional commitment in the operating room nurses in teaching hospitals. Study Design. The present study used a descriptive-correlational design. Participants were selected via census sampling from hospitals in Shiraz over a period of three months. The participants were 350 operating room nurses who met the inclusion criteria. Data were collected using professional communication and a professional commitment questionnaire. The collected data were analyzed using the descriptive and inferential statistics in SPSS vv. 22. Findings. The operating room nurses' mean scores for professional communication (136.81 ± 13.77) and professional commitment (71.42 ± 11.62) were found to be high. The results of the Pearson correlation coefficient test showed that there was a statistically significant linear relationship between professional communication and professional commitment (p<0.001, r = 0.235). The results also showed that there was a significant relationship between professional commitment on the one hand and gender (p=0.042), marital status (p=0.047), and interest in work (p=0/000) on the other hand. There was also a significant relationship between professional communication and interest in work (p=0/000). Conclusion. Given the significance of professional communication and professional commitment in the operating rooms, it is recommended that healthcare administrators and policymakers take steps to improve these areas. It is suggested that measures should be taken to increase the personnel's awareness of the principles of professional communication and the significance of professional commitment through regular workshops.